Coordination modulated on-off switching of flexibility in a metal–organic framework. Issue 44 (4th November 2021) - Albalad, Jorge; Peralta, Ricardo A.; Huxley, Michael T.; Tsoukatos, Steven; Shi, Zhaolin; Zhang, Yue-Biao; Evans, Jack D.; Sumby, Christopher J.; Doonan, Christian J.
Abstract : Stimuli-responsive metal–organic frameworks (MOFs) exhibit dynamic structural changes upon exposure to external stimuli. Here the coordination geometry of a post-synthetically added metal ion drastically changes the adsorption properties. Abstract : Stimuli-responsive metal–organic frameworks (MOFs) exhibit dynamic, and typically reversible, structural changes upon exposure to external stimuli. This process often induces drastic changes in their adsorption properties. Herein, we present a stimuli-responsive MOF, 1 ·[CuCl], that shows temperature dependent switching from a rigid to flexible phase. This conversion is associated with a dramatic reversible change in the gas adsorption properties, from Type-I to S-shaped isotherms. The structural transition is facilitated by a novel mechanism that involves both a change in coordination number (3 to 2) and geometry (trigonal planar to linear) of the post-synthetically added Cu(i ) ion. This process serves to 'unlock' the framework rigidity imposed by metal chelation of the bis-pyrazolyl groups and realises the intrinsic flexibility of the organic link.